GE_GERICHTE PS/54/2022 vom 28. Juli 2021 - GE Cour de justice (2021)
MESURE THÉRAPEUTIQUE INSTITUTIONNELLE;SOINS MÉDICAUX;TRAITEMENT FORCÉ;COMPÉTENCE RATIONE MATERIAE | CP.59.al2; LS.50; LS.51; REPM.4.al1; REPM.4.al6